2005
DOI: 10.1074/jbc.m411047200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Peptide Isolated from a Phage Display Peptide Library with Trastuzumab Can Mimic Antigen Epitope of HER-2

Abstract: Trastuzumab, a humanized antibody to HER-2, has been shown to be effective in the treatment of breast cancer in which HER-2 overexpression and metastasis occurs. In our search for an effective mimic epitope of HER-2 binding with trastuzumab and to develop HER-2 peptide vaccine, we screened a phage display 12-mer peptide library with trastuzumab as the target. A mimetic peptide (mimotope) H98 (LLGPYELWELSH) that could specifically recognize trastuzumab was isolated. The DNA encoding peptide H98 was cloned and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 20 publications
(32 reference statements)
0
44
0
Order By: Relevance
“…In addition, several HER-2 B cell mimotopes have been identified through phage display (11,52,53). Riemer et al (52) used a constrained 10-mer random peptide phage display library to identify peptide mimotopes to trastuzumab; Abs raised against one of these peptides recognized HER-2/neu and caused internalization of the receptor from the cell surface in a similar manner as trastuzumab (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several HER-2 B cell mimotopes have been identified through phage display (11,52,53). Riemer et al (52) used a constrained 10-mer random peptide phage display library to identify peptide mimotopes to trastuzumab; Abs raised against one of these peptides recognized HER-2/neu and caused internalization of the receptor from the cell surface in a similar manner as trastuzumab (52).…”
Section: Discussionmentioning
confidence: 99%
“…Although this peptide sequence bears no sequence homology to HER-2, it was matched to the third loop of HER-2 at the HER-2/trastuzumab interface using computational methods (54). Jiang et al (53) identified another mimotope that matched to an epitope between loops 1 and 2 of HER-2 at the HER-2/trastuzumab interface. These studies indicate that all three loops are important for trastuzumab-binding HER-2.…”
Section: Discussionmentioning
confidence: 99%
“…These five amino acids are considered to be the minimal sequence essential for binding to the antibody. Epitope mappings using random peptide display libraries have been reported for several antibodies, and a number of binding peptides for each antibody have been isolated (Stephen et al 1995;Jiang et al 2005;Ja et al 2005;Bimder et al 2006). However, the identification of cross-reacting antigen candidates as annotated polypeptides has not been reported.…”
Section: Alignments Of Isolated Clonesmentioning
confidence: 99%
“…Many protein-display systems with random peptide libraries have been used for epitope mapping (Stephen et al 1995, Jiang et al 2005Ja et al 2005;Bimder et al 2006). However, by using random peptide libraries, it has been difficult to identify cross-reacting antigens as annotated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of these studies is to use a peptide immunogen, instead of whole antigen (Agn), to produce Abs that cross-react with a single restricted epitope on a protein. For example, peptides are being used to produce Abs against specific epitopes on tumor Agns that decrease cell proliferation [10][11][12][13]. Peptides are also used as alternatives to CHO Agns because they can elicit a T-cell dependent immune response along with CHO-cross-reactive Abs [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%